Preparation method of peach-radix angelicae silk nanofiber mask

The preparation of Taozhi silk nanofiber masks through electrospinning has solved the problems of insufficient functional and poor stability of active ingredients in the existing nanofiber masks, and achieved higher breathability, moisturizing and skin care effects.

CN119632853APending Publication Date: 2025-03-18洛兮生命科技(杭州)有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411824016.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing nanofiber masks still have insufficient functionality, and the stability of the active ingredients is poor, which affects the skin care effect.

Method used

Electrospinning method is used to prepare peach angelica silk nanofiber mask. By mixing peach gum powder, angelica powder and silk fibroin solution in a specific proportion, and optimizing the electrospinning process, we ensure the uniform distribution and stable embedding of the active ingredients.

Benefits of technology

It significantly improves the stability and release efficiency of active ingredients in the mask, enhances the breathability, moisturizing and skin care effects of the mask, and maintains the fit and breathability of the mask.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119632853A_ABST
    Figure CN119632853A_ABST
Patent Text Reader

Abstract

According to the preparation method of the peach gum-angelica dahurica silk nanofiber mask, the raw material proportion of peach gum, angelica dahurica and silk nanofiber is accurately controlled, the silk nanofiber preparation process and electrostatic spinning parameters are optimized, and the mask with the fiber diameter within the range of 50-65 nm is prepared. The mask integrates the moisturizing and nourishing properties of the peach gum, the whitening and anti-inflammatory properties of the angelica dahurica and the excellent properties of the silk nanofibers, ensures the stability and the antioxidant effect of natural plant active ingredients such as the peach gum and the angelica dahurica in the nanofibers, remarkably improves the air permeability and the moisturizing capacity, and provides a new scheme for modern skin care. Compared with a contrast, the mask provided by the embodiment of the invention has excellent air permeability, liquid carrying rate, wet tensile strength and DPPH clearance rate, and meets the requirements of green production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of daily chemical facial masks, and particularly relates to a method for preparing a peach and angelica silk nanofiber facial mask. Background Art

[0002] With the acceleration of modern life and the intensification of environmental pollution, people's demand for skin care is increasing, and the quality requirements for skin care products are getting higher and higher. As an important part of daily skin care, the performance of facial masks is directly related to the health and beauty of the skin. Although traditional facial mask materials, such as cotton cloth and non-woven fabrics, can meet basic skin care needs to a certain extent, they still have many shortcomings in terms of breathability, moisturizing, facial fit and functionality.

[0003] In order to improve the performance of facial masks, researchers are constantly exploring new mask materials. Among them, nanofiber materials have become a hot topic in mask material research due to their unique nanoscale structure, excellent air permeability and moisturizing properties. Nanofiber masks can fit closely to the skin, forming a thin and breathable film that effectively prevents water evaporation while promoting the skin's absorption of nutrients.

[0004] However, most of the nanofiber masks on the market currently use a single nanofiber material, such as polyester, polypropylene and other synthetic fibers. Although these materials have good physical properties, their functionality still needs to be improved. In addition, although some nanofiber masks have added active ingredients such as plant extracts, due to the limitations of the preparation method and process, the stability of these active ingredients in the mask is often poor, affecting the skin care effect of the mask. Summary of the invention

[0005] In view of the above technical problems, the present invention proposes a method for preparing a peach silk nanofiber mask, which is achieved through the following technical solutions:

[0006] A peach zhi silk nanofiber facial mask, the preparation method of which specifically comprises the following steps:

[0007] S1 Raw material preparation: Select dried peach gum, ultrasonically clean for 20 minutes to remove impurities and pedicles, wash with warm water, microwave dry to a moisture content of 6% to 8%, grind with an ultrafine grinder for 30 minutes to grind the peach gum to a particle size of 800 to 1000 mesh. Wash angelica dahurica, remove impurities on the surface, and dry with hot air to a moisture content of 13% to 15%. Slice the dried angelica rootstock to a thickness of 2 mm, and grind with a grinder to a particle size of 1000 to 1200 mesh.

[0008] S2 Preparation of silk nanofibers: First, select high-quality natural silk, remove impurities, broken silk and thick silk that does not meet the requirements, and ensure the purity and uniformity of the silk used. Then, place the selected silk in a silk fibroin solution containing 8wt% to 12wt% and pH = 7.5 to 7.7, preferably a 2M LiBr solution, and immerse for 1 hour to dissolve the silk into a silk fibroin solution and remove undissolved particles or impurities.

[0009] S3 electrospinning: Peach gum powder, Angelica dahurica powder and silk fibroin solution were fully mixed in a volume ratio of 1:1:(5-15); a 10mL medical syringe was used to evenly inhale the mixture, and the voltage was adjusted to 20KV, the solution flow rate to 1mL / h, the receiving distance to 12-20cm, and the drum winding speed to 150r / min. The collected fiber membrane was then gently removed and placed in an oven at 55℃-60℃ for drying. After drying, it was placed in a sealed bag for low-temperature storage to prepare a peach dahurica silk nanofiber mask with a fiber diameter in the range of 50-65nm.

[0010] Preferably, in step S3, the volume ratio of peach gum powder, angelica dahurica powder and silk fibroin solution is 1:1:(10-15).

[0011] Preferably, the receiving distance in step S3 is 15-18 cm.

[0012] Beneficial effects:

[0013] The present invention provides a preparation method of a peach and angelica silk nanofiber mask, which integrates the moisturizing and nourishing properties of peach gum, the whitening and anti-inflammatory effects of angelica and the excellent performance of silk nanofibers, and also significantly improves the stability of active ingredients in the mask. By mixing peach gum powder and angelica powder with a silk fibroin solution in a precise ratio and optimizing the electrostatic spinning process, the present invention effectively ensures the uniform distribution and stable embedding of natural active ingredients such as peach gum and angelica in the mask fibers. This fine processing method not only prevents the loss and degradation of active ingredients during preparation and storage, but also greatly improves their release efficiency and bioavailability when in contact with the skin. In addition, silk nanofibers are used as carriers, and their unique nanoscale structure and good biocompatibility provide a stable and efficient transmission platform for active ingredients. This not only helps to maintain the fit and breathability of the mask on the skin, but also promotes the penetration and absorption of active ingredients into the skin layer, thereby further enhancing the skin care effect of the mask. In summary, the present invention not only improves the basic performance of the facial mask through an innovative preparation method and optimized process parameters, but also significantly enhances the stability of the active ingredients in the facial mask and the skin care effect, providing a new, efficient and stable solution for the field of modern skin care. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The fiber SEM images of the Taozhi silk nanofiber mask prepared in Examples 1 to 3; Figure 1 a is a fiber SEM image of the Taozhi silk nanofiber mask prepared in Example 1; Figure 1 b is a fiber SEM image of the Taozhi silk nanofiber mask prepared in Example 2; Figure 1 c is the fiber SEM image of the Taozhi silk nanofiber mask prepared in Example 3. DETAILED DESCRIPTION

[0015] The technical solution proposed in the present invention is further described below in conjunction with the embodiments, but it is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the protection scope of the present invention. Unless otherwise specified in the following embodiments, the technical means used in the embodiments of the present invention are conventional means well known to those skilled in the art.

[0016] Example 1: A method for preparing a peach silk nanofiber mask

[0017] S1 Raw material preparation: Select dried peach gum, ultrasonically clean for 20 minutes to remove impurities and pedicles, wash with warm water, microwave dry to a moisture content of 6%, grind with an ultrafine grinder for 30 minutes, grind the peach gum to a particle size of 1000 mesh. Wash angelica dahurica, remove impurities on the surface, dry with hot air to a moisture content of 13%, slice the dried angelica rootstock, slice thickness 2 mm, grind with a grinder to a particle size of 1200 mesh.

[0018] S2 Preparation of silk nanofibers: First, select high-quality natural silk, remove impurities, broken silk and thick silk that does not meet the requirements, and ensure the purity and uniformity of the silk used. Then, place the selected silk in a silk fibroin solution containing 8wt% and pH=7.5, preferably a 2M LiBr solution, and immerse for 1 hour to dissolve the silk into a silk fibroin solution and remove undissolved particles or impurities.

[0019] S3 electrospinning: Peach gum powder, Angelica dahurica powder and silk fibroin solution were mixed thoroughly in a volume ratio of 1:1:10; a 10mL medical syringe was used to evenly inhale the mixture, and the voltage was adjusted to 20KV, the solution flow rate to 1mL / h, the receiving distance to 15cm, and the drum winding speed to 150r / min. The collected fiber membrane was then gently removed and placed in an oven at 55°C for drying. After drying, it was placed in a sealed bag for low-temperature storage to prepare the peach and angelica silk nanofiber mask.

[0020] Example 2: A method for preparing a peach silk nanofiber mask

[0021] S1 Raw material preparation: Select dried peach gum, ultrasonically clean for 20 minutes to remove impurities and pedicles, wash with warm water, microwave dry to a moisture content of 7%, grind with an ultrafine grinder for 30 minutes, grind the peach gum to a particle size of 900 mesh. Wash angelica dahurica, remove impurities on the surface, dry with hot air to a moisture content of 14%, slice the dried angelica rootstock, slice thickness 2 mm, grind with a grinder to a particle size of 1100 mesh.

[0022] S2 Preparation of silk nanofibers: First, select high-quality natural silk, remove impurities, broken silk and thick silk that does not meet the requirements, and ensure the purity and uniformity of the silk used. Then, place the selected silk in a 10wt% silk fibroin solution with a pH of 7.6, preferably a 2M LiBr solution, and immerse for 1 hour to dissolve the silk into a silk fibroin solution and remove undissolved particles or impurities.

[0023] S3 electrospinning: Peach gum powder, Angelica dahurica powder and silk fibroin solution were fully mixed in a volume ratio of 1:1:12.5; a 10mL medical syringe was used to evenly inhale the mixture, and the voltage was adjusted to 20KV, the solution flow rate to 1mL / h, the receiving distance to 17cm, and the drum winding speed to 150r / min. The collected fiber membrane was then gently removed and placed in an oven at 58°C for drying. After drying, it was placed in a sealed bag for low-temperature storage to prepare the peach and angelica silk nanofiber mask.

[0024] Example 3: A method for preparing a peach silk nanofiber mask

[0025] S1 Raw material preparation: Select dried peach gum, ultrasonically clean for 20 minutes to remove impurities and pedicles, wash with warm water, microwave dry to 8% water content, grind with superfine grinder for 30 minutes to grind peach gum to 800 mesh. Wash angelica dahurica, remove impurities on the surface, dry with hot air to 15% water content, slice the dried angelica rootstock, slice thickness 2 mm, grind with grinder to 1000 mesh.

[0026] S2 Preparation of silk nanofibers: First, select high-quality natural silk, remove impurities, broken silk and thick silk that does not meet the requirements, and ensure the purity and uniformity of the silk used. Then, place the selected silk in a 12wt% silk fibroin solution with a pH of 7.7, preferably a 2M LiBr solution, and immerse for 1 hour to dissolve the silk into a silk fibroin solution and remove undissolved particles or impurities.

[0027] S3 electrospinning: Peach gum powder, Angelica dahurica powder and silk fibroin solution were fully mixed in a volume ratio of 1:1:15; a 10mL medical syringe was used to evenly inhale the mixture, and the voltage was adjusted to 20KV, the solution flow rate to 1mL / h, the receiving distance to 18cm, and the drum winding speed to 150r / min. The collected fiber membrane was then gently removed and placed in an oven to dry at 60°C. After drying, it was placed in a sealed bag for low-temperature storage to prepare the peach and angelica silk nanofiber mask.

[0028] Comparative Example 1: Exploring the effect of electrospinning at different receiving distances on the preparation of Taozhi silk nanofiber mask

[0029] S1 Raw material preparation: Select specially treated dried peach gum, perform ultrasonic cleaning for 20 minutes to remove impurities and pedicles, wash with warm water, microwave dry to 7% moisture content, and use ultrafine grinder to grind to 900 mesh. For Angelica dahurica raw material, remove impurities, wash, dry with hot air to 14% moisture content, slice to 2mm thickness, and grind to 1100 mesh.

[0030] Preparation of S2 silk nanofibers: Select high-quality natural silk, remove impurities, and immerse the selected silk in a 10wt% silk fibroin solution with a pH of 7.6. Use LiBr solution to immerse for 1 hour to dissolve the silk into a silk fibroin solution and remove undissolved particles and impurities.

[0031] S3 electrospinning: Peach gum powder: Angelica dahurica powder: Silk fibroin solution was fully mixed in a volume ratio of 1:1:12.5, and the mixture was evenly inhaled using a 10mL medical syringe. The voltage was adjusted to 20KV, the solution flow rate was 1mL / h, the receiving distances were 12cm and 20cm respectively, and the drum winding speed was 150r / min. After the electrospinning was completed, the fiber membrane was removed and placed under 58℃ drying conditions for drying.

[0032] Comparative Example 2: Exploring the effects of different raw material ratios in electrospinning on the preparation of Taozhi silk nanofiber mask

[0033] S1 Raw material preparation: Select specially treated dried peach gum, perform ultrasonic cleaning for 20 minutes to remove impurities and pedicles, wash with warm water, microwave dry to 7% moisture content, and use ultrafine grinder to grind to 900 mesh. For Angelica dahurica raw material, remove impurities, wash, dry with hot air to 14% moisture content, slice to 2mm thickness, and grind to 1100 mesh.

[0034] Preparation of S2 silk nanofibers: Select high-quality natural silk, remove impurities, and immerse the selected silk in a 10wt% silk fibroin solution with a pH of 7.6. Use LiBr solution to immerse for 1 hour to dissolve the silk into a silk fibroin solution and remove undissolved particles and impurities.

[0035] S3 electrospinning: Peach gum powder: Angelica dahurica powder: Silk fibroin solution was fully mixed in a volume ratio of 1:1:5, and the mixture was evenly inhaled using a 10mL medical syringe. The voltage was adjusted to 20KV, the solution flow rate was 1mL / h, the receiving distance was 17cm, and the drum winding speed was 150r / min. After the electrospinning was completed, the fiber membrane was removed and dried at 58℃ to study the effect of drying conditions on the performance of the mask.

[0036] Comparative Example 3: Example 2 was used as the control group, peach gum was not added, and other processes were normal.

[0037] Comparative Example 4: Example 2 was used as the control group, without adding Angelica dahurica, and other processes were normal.

[0038] Example 4: Fiber morphology characterization

[0039] The peach zhi silk nanofiber mask prepared in Examples 1 to 3 was dried in a vacuum drying oven at 35°C for 6 hours to remove the residual solvent, and then prepared into a sample, the surface was gold-sprayed, the acceleration voltage was 3 kV, and the morphology was characterized using a scanning electron microscope (SEM).

[0040] The peach zhi silk nanofiber masks prepared in Examples 1 to 3 were characterized and analyzed in detail. Figure 1 The SEM images of the Taozhi silk nanofiber mask prepared under different conditions in Examples 1 to 3 show that all fibers are randomly distributed and disorderly interlaced. For Example 1, the nanofibers were measured using Image J software to be about 62 nm ( Figure 1 a); for Example 2, the nanofibers were measured using Image J software to be approximately 65 nm ( Figure 1 b); for Example 3, the nanofibers were measured using Image J software to be about 50 nm ( Figure 1 c). According to the method for preparing the peach zhi silk nanofiber mask proposed in the present invention, a mask with a fiber diameter of 50 to 65 nm is prepared. The fiber diameter within this range ensures both the permeability and breathability of the mask as well as the strength and durability of the mask.

[0041] Example 5: Performance Test

[0042] Air permeability test: refer to GB / T5354 test. Before the test, place the sample in an environment with a temperature of 20℃ and a relative humidity of 65% to achieve equilibrium. Use an air permeability tester to test the area of ​​20cm 2 , pressure 100Pa;

[0043] Liquid carrying rate test: refer to GB / T24218.6-2010 test, cut the sample into 10cm×10cm, weigh it as m0, put the mask base fabric into a closed culture dish filled with deionized water and soak it for 10s, then hang the sample vertically, drip off the excess deionized water for 120s, weigh it again and record it as m1, calculate the liquid carrying rate (LAC), the liquid carrying rate calculation formula is: LAC=(m1-m0) / m0;

[0044] Wet tensile strength: Soak in deionized water for 20 minutes at a temperature of 20°C and a relative humidity of 65%, take it out and hang it vertically until there is no continuous water droplets dripping, and test the tensile strength with a tensile strength tester at a rate of 50mm / min;

[0045] Antioxidant activity: Characterized by DPPH free radical scavenging ability. Take a 96-well plate, add 100μLDPH solution and 100μL anhydrous ethanol solution, add the sample, and shake on a shaker for 30 minutes (protected from light). Use an enzyme reader to measure its absorbance at 517nm. The DPPH free radical scavenging ability calculation formula is: (D0-(D1-D2)) / D0×100%, where D0 is the absorbance of 100μLDPH solution + 100μL anhydrous ethanol, D1 is the absorbance of 100μLDPH solution + sample; D2 is the absorbance of sample + 100μL anhydrous ethanol, and the positive control solution is 1mg / mL VC solution.

[0046] All the measurement results are as follows:

[0047] Table 1

[0048]

[0049]

[0050] The present invention prepares a peach silk nanofiber mask by electrospinning, which gives it higher air permeability, moisture retention, facial fit and antioxidant properties. The peach silk nanofiber mask material prepared by the present invention is a biodegradable material, which meets the requirements of green production.

[0051] It can be seen from the table data that the peach silk fiber mask represented by Example 1, Example 2 and Example 3 is significantly better than the two samples in Comparative Example 1 in terms of air permeability, liquid carrying rate, wet tensile strength and DPPH removal rate. Among them, the mask prepared by Example 2 has better comprehensive performance in various aspects, indicating that the mask of the embodiment has better gas exchange capacity, which helps the skin breathe; it can carry and release more skin care liquid, and improve the skin care effect; the mask of the embodiment (4.36~4.92N / cm) is tougher and less prone to damage than Comparative Example 1 (3.25~3.78N / cm); in addition, the DPPH removal rate of the embodiment is above 96.8%, which is higher than 90.7~92.1% of Comparative Example 1, indicating that the mask of the embodiment has stronger antioxidant properties and can better protect the skin from free radical damage. These differences are due to the use of more suitable conditions for the receiving distance in the electrospinning process of Examples 1 to 3, thereby optimizing the various properties of the mask.

[0052] By comparing the embodiment with comparative example 2 (different raw material ratios), it can be found that the peach silk fiber mask of the embodiment also shows superiority in terms of air permeability, liquid carrying rate, wet tensile strength and DPPH removal rate. These differences may be due to the use of more suitable conditions for the raw material ratio in the electrospinning process of embodiments 1 to 3, thereby optimizing the various properties of the mask.

[0053] By comparing the embodiment with comparative examples 3 and 4 (with or without peach gum / angelica), it can be found that the peach and angelica silk nanofiber mask of the embodiment is obviously superior in terms of air permeability, liquid carrying rate, wet tensile strength and DPPH clearance rate. These differences may be due to the fact that only silk fibers and a single raw material (peach gum and angelica) are added to the comparative example, which affects the air permeability, liquid carrying rate, wet tensile strength and DPPH clearance rate of the nanofiber mask, further illustrating the superior performance of the peach and angelica silk nanofiber mask prepared by the present invention.

[0054] Example 6: Evaluation of active ingredients

[0055] Total phenol has an antioxidant effect. The higher the total phenol content, the stronger the antioxidant performance. Peach gum and Angelica dahurica contain a variety of phenolic compounds. The total phenol content of the peach and Angelica dahurica silk nanofiber mask prepared by the present invention was measured. Take 50 μL of the mask liquid of Examples 1 to 3 and Comparative Examples 1 to 4 respectively, add 50 μL of distilled water, add 500 μL of 10% Folin phenol reagent, mix well and let stand for 5 minutes, then add 400 μL of 7.5% Na2CO3 solution, mix well and keep away from light for 40 minutes, and measure its absorbance at a wavelength of 765 nm. Using gallic acid as the standard, draw a standard curve, and get the gallic acid regression equation: y=5.4910x+0.0731, R 2=0.9998. The total phenol content in each group of mask liquid was calculated using the gallic acid standard curve, in mg / mL.

[0056] The results are as follows:

[0057] Table 2

[0058]

[0059] By comparing the Taozhi silk nanofiber masks prepared under different conditions, this experiment found that the masks prepared in Examples 1 to 3 all showed a high level of total phenol content, which directly reflects the retention and extraction efficiency of the effective ingredients in the masks. Among them, the total phenol content of Example 2 was the highest, reaching 35.55 mg / g, which may be due to the optimal combination of its raw material ratio, silk nanofiber preparation process and electrospinning parameters.

[0060] By changing the receiving distance, Comparative Example 1 found that when the receiving distance was 12 cm and 20 cm, the total phenol content of the mask was lower than that of Example 2, indicating that the receiving distance had a certain influence on the retention of the active ingredients in the mask, and under the experimental conditions, a receiving distance of 15 cm to 18 cm may be more conducive to the retention of the active ingredients.

[0061] By changing the raw material ratio, Comparative Example 2 found that when the ratio of peach gum powder and angelica powder was reduced, the total phenol content of the mask also decreased accordingly, which further confirmed the important role of peach gum and angelica in the mask, and the influence of the raw material ratio on the performance of the mask.

[0062] Comparative Examples 3 and 4 did not add peach gum and Angelica dahurica respectively. The results showed that the total phenol content of the mask was significantly reduced, even lower than the lowest value in Comparative Example 1, which fully demonstrated the importance of peach gum and Angelica dahurica in improving the total phenol content and overall performance of the mask.

Claims

1. A method for preparing a peach silk nanofiber mask, characterized in that: The following steps are involved: S1 raw material preparation: select dried peach gum and angelica dahurica, wash, dry and crush them to obtain peach gum powder with a particle size of 800-1000 mesh and angelica dahurica powder with a particle size of 1000-1200 mesh; S2 Preparation of silk nanofibers: Select high-quality natural silk, remove impurities, and then dissolve it in a silk fibroin solution containing 8wt% to 12wt% and pH = 7.5 to 7.7 to form a silk fibroin solution; S3 electrospinning: Peach gum powder, angelica powder and silk fibroin solution were mixed in a volume ratio of 1:1:(5-15), and a nanofiber mask with a fiber diameter in the range of 50-65 nm was prepared by electrospinning technology.

2. The preparation method according to claim 1, characterized in that: In step S1, the peach gum is microwave dried to a moisture content of 6% to 8%, and the angelica dahurica is hot-air dried to a moisture content of 13% to 15%.

3. The preparation method according to claim 1, characterized in that: In step S2, the silk fibroin solution is a 2M LiBr solution, and the immersion time is 1 hour.

4. The preparation method according to claim 1, characterized in that: In step S3, the volume ratio of peach gum powder, angelica dahurica powder and silk fibroin solution is 1:1:(10-15).

5. The preparation method according to claim 1, characterized in that: In step S3, the electrospinning parameters include voltage 20 KV, solution flow rate 1 mL / h, receiving distance 12-20 cm, and drum winding speed 150 r / min.

6. The preparation method according to claim 5, characterized in that: The electrospinning receiving distance is 15 to 18 cm.

7. The preparation method according to claim 1, characterized in that: After step S3, the collected fiber membranes are dried at 55° C. to 60° C. and placed in a sealed bag for low-temperature storage.